ALCOR Project: Contributions to Optimizing Remote Robot Guidance in Intelligent Spaces - Felipe Espinosa Zapata; José Luis Lázaro Galilea; Joaquín Olivares Bueno (Revista Iberoamericana de Automática e Informática Industrial RIAI)
The work shows the sensory, communication and control solutions for the remote guidance of robots in intelligent environments, as derived activity from the ALCOR project. In this type of applications, optimizing shared resources, especially those related to energy autonomy and the use of the wireless channel, remains a challenge. The main contributions of the project are: a) development of sensorial units based on infrared with centimeter accuracy in the location of the source and response times of milliseconds; b) wireless communication solutions that improve the information routing and homogenization in network traffic; and c) control and estimation solutions based on events with independent mechanisms of action on the mobile unit and request for measurements to the sensor module. The commercial robot P3-DX has been used for experimental tests.